Daily alcohol intake and its negative association with constipation based on NHANES data 2005–2010 - Wen-Xing Chen; Xue-Feng Peng; Miao Yu; Deng-Chao Wang (Scientific Reports)
Abstract Constipation is a common gastrointestinal disorder that causes both physical and psychological distress to many patients, significantly affecting their daily lives and quality of life. Alcohol consumption is often considered a potential factor in various health issues; however, its association with constipation has not been adequately studied in large-scale population research. This study aims to investigate the association between daily alcohol intake and constipation in adults by analyzing data from the 2005–2010 National Health and Nutrition Examination Survey (NHANES). Data from NHANES participants aged over 20 years from 2005 to 2010 were analyzed. Weighted logistic regression models were used to assess the association between daily alcohol intake and constipation, calculating odds ratios (OR) and 95% confidence intervals (CI) while adjusting for potential confounders. Additionally, restricted cubic splines (RCS) were applied to explore potential nonlinear patterns in the alcohol-constipation relationship, and subgroup analyses were conducted to assess effect differences across various population groups. Potential interaction factors within different subgroups were also examined. A total of 14,465 participants were included in the study. After adjusting for multiple confounders, a significant inverse association was found between daily alcohol intake (as a continuous variable) and constipation, with an OR of 0.98 (95% CI: 0.96–0.99, P = 0.005). Compared to non-drinkers (Q1), the risk of constipation progressively decreased among light (Q2), moderate (Q3), heavy (Q4), and very heavy drinkers (Q5). In our analysis, the OR for the heaviest drinkers (Q5) was 0.24 (95% CI: 0.11–0.52, P < 0.001), with a significant trend test (P = 0.001). RCS analysis revealed a significant nonlinear inverse relationship between alcohol intake and constipation (P = 0.016). No significant interactions were observed in the subgroup analysis (all P-values > 0.05). This study identified a significant inverse association between daily alcohol intake and constipation. Future research should employ more rigorous designs, such as prospective cohort studies, to confirm the association between alcohol intake and gut health and to elucidate the underlying biological mechanisms to assess the potential benefits and risks of alcohol consumption.